Case of the coronary artery aneurysm stenting - E. V. Aksjonov; O. V. Levchyshyna (Ukrainian Journal of Cardiovascular Surgery, 2016)
The article presents a case of diagnosе and treating of the patient with an aneurysm of the infrarenal aorta and coronary artery aneurysm.